Karakter Visual Keindonesiaan dalam Iklan Cetak di Indonesia - Suwardikun, Didit Widiatmoko (Journal of Visual Art and Design, 2008)
Many have tried to explore the unified identity character of an Indonesian, arousing certain tribal cultures to visually represent "Indonesian" on apparent bestowed upon Indonesia as a nation of multi-cultures. This is clearly be seen in advertisements where the expressed visuals represent periods, societal forms, political, and economical situation according to the allotted time and space. Thus, visuals on advertisements may serve as clues to understand the significance of expressions as "Indonesian" out of the memory of how things were and were done and therefore ought to be done. This study explores visuals from the advertisements of the past to understand the spirit of Indonesia as a nation for the purpose of tomorrow. The study looked into visuals of the advertisements from the Dutch colonial era, Japanese occupation period, the birth of a nation in 1950s, the new order (1970s-1990s), and end with those of reform order (2000s); in order to portray "Indonesian" in terms of figure, behavior, and attitude of a nation. The paper discusses visuals of the past to model the present and future of an "Indonesian".